2019
DOI: 10.1016/j.drudis.2018.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of circulating tumor cells as a reflection of the tumor heterogeneity: myth or reality?

Abstract: Oncology has entered in the era of personalized medicine with its advantages such as limited invasiveness during sample collection, robustness, precision and speed. This new era has led to novel practices of tissue sampling (e.g. needle biopsy) and the main goal of diagnostic medicine is now to detect crucial events in "infinitely" small samples. The key question is now to determine if the rare cell events isolated and characterized from these samples are reliably reflecting the initial and/or metastatic disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 67 publications
0
37
0
Order By: Relevance
“…Single-cell analyses have revealed that CTCs often comprise a heterogeneous population of cells. Logically, this heterogeneity may reflect the extent of intratumor heterogeneity (ITH) [65][66][67][68][69][70] and may have important implications for prognosis and resistance to therapy. Indeed, a recent study of archived samples from patients with metastatic breast cancer found 85% concordance between CTCs and metastatic sites in terms of mutations and copy-number profile [71].…”
Section: Ctc Heterogeneitymentioning
confidence: 99%
See 2 more Smart Citations
“…Single-cell analyses have revealed that CTCs often comprise a heterogeneous population of cells. Logically, this heterogeneity may reflect the extent of intratumor heterogeneity (ITH) [65][66][67][68][69][70] and may have important implications for prognosis and resistance to therapy. Indeed, a recent study of archived samples from patients with metastatic breast cancer found 85% concordance between CTCs and metastatic sites in terms of mutations and copy-number profile [71].…”
Section: Ctc Heterogeneitymentioning
confidence: 99%
“…An additional study of metastatic breast cancer reported 85% concordance in single-nucleotide variant (SNV) mutations and copy-number alterations (CNAs) between paired CTCs and metastases [71]. However, as mentioned earlier, CTC profiling may not always recapitulate the heterogeneity of the entire tumor or metastatic lesion because of the low number of CTCs isolated from blood and the lack of statistical power to cover all tumor regions uniformly [67,71].…”
Section: Clinical Value Of Ctcsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the clonal evolution of cancers is tightly controlled by the selective pressure of the local microenvironment (e.g. immune infiltrate, hypoxia), and can be oriented under drug pressure toward resistant or tolerant cancer cells (20,21). Regardless of what the first oncogenic event is, a permissive local micro-environment is obligatory for protecting cancer-initiating cells against immune cells and fuelling these cells with adequate nutrients (22).…”
Section: Clonal Evolution Of Cancer Cells In Osteosarcoma: a Combinatmentioning
confidence: 99%
“…This indicates that CD44 (+) /CD45 (−) CTCs functionally resemble or potentially are CSCs. Therefore, CTCs can mimic the genetic features of tumors at a given time and represent the current state of disease [86]. CTCs cultured in vitro can be used for drug sensitivity screening, a promising approach toward precision medicines.…”
Section: Ctc Assay For Prognosis and Treatment Management Of Gcmentioning
confidence: 99%